Pretransplant Portal Vein Recanalization—Transjugular Intrahepatic Portosystemic Shunt in Patients With Complete Obliterative Portal Vein Thrombosis. Issue 11 (November 2015) - Salem, Riad; Vouche, Michael; Baker, Talia; Herrero, Jose Ignacio; Caicedo, Juan Carlos; Fryer, Jonathan; Hickey, Ryan; Habib, Ali; Abecassis, Michael; Koller, Felicitas; Vogelzang, Robert; Desai, Kush; et al.
Abstract : Background: Chronic, obliterative portal vein (PV) thrombosis (PVT) represents a relative contraindication to liver transplantation (LT) in some centers. When PV thromboembolectomy is not feasible, alternative techniques (portacaval hemitransposition, portal arterialization, multivisceral transplantation) are associated with suboptimal outcomes. In cases where a chronically thrombosed PV has become obliterated, we developed PV recanalization (PVR)-transjugular intrahepatic portosystemic shunt (TIPS) to potentiate LT. We evaluated the impact of PVR-TIPS on liver function, transplant eligibility, and long-term outcomes after LT. Methods: Forty-four patients with chronic obliterative main PVT were identified during our institutional LT selection committee. After joint imaging review by transplant surgery/radiology, these patients underwent PVR-TIPS to potentiate transplant eligibility. Patients were followed by hepatology/transplant until LT, and ultimately in posttransplant clinic. The TIPS venography and serial ultrasound/MRI were used subsequently to document PV patency. Results: The main PV (MPV) was completely thrombosed in 17 of 44 (39%) patients; near complete (>95%) occlusion was noted in 27 of 44 (61%) patients. Direct transhepatic and transsplenic punctures were required in 11 of 43 (26%) and 3 of 43 (7%) cases, respectively. Technical success was 43 of 44 (98%) cases. At PVR-TIPS completion, persistence of MPV thrombus was noted in 33 of 43 (77%) cases. One-month TIPS venography demonstrated complete resolution of MPV thrombosis in 22 of 29 (76%) without anticoagulation. Thirty-six patients were listed for transplantation; 18 (50%) have been transplanted. Eighty-nine percent MPV patency rate and 82% survival were achieved at 5 years. Conclusions: The PVR-TIPS may be considered for patients with obliterative PVT who are otherwise appropriate candidates for LT. The high rate of MPV patency post-TIPS placement suggests flow reestablishment as the dominant mechanism of thrombus resolution. Abstract : Portal vein recanalization-transjugular intrahepatic portosystemic shunt (PVR-TIPS) should be indicated for liver transplant candidates with chronic, obliterative portal vein thrombosis (PVT) to potentiate liver transplant eligibility and provides complete resolution of MPV thrombosis in most cases. Supplemental digital content is available in the text.